Human Gut Microbial Degradation of Flavonoids: Structure−Function Relationships - Simons, Andrean L; Renouf, Mathieu; Hendrich, Suzanne; Murphy, Patricia A (Journal of agricultural and food chemistry, 2005)
The relationship between chemical structure and gut microbial degradation rates of 14 flavonoids, flavone, apigenin, chrysin, naringenin, kaempferol, genistein, daidzein, daidzin, puerarin, 7,4‘-dihydroxyflavone, 6,4‘-dihydroxyflavone, 5,4‘-dihydroxyflavone, 5,3‘-dihydroxyflavone, and 4‘-hydroxyflavone, was investigated by anaerobically fermenting the flavonoids with human gut microflora (n = 11 subjects). Degradation rates for the 5,7,4‘-trihydroxyl flavonoids, apigenin, genistein, naringenin, and kaempferol, were significantly faster than the other structural motifs. Puerarin was resistant to degradation by the gut microflora. Extensive degradation of flavonoids by gut microflora may result in lower overall bioavailability than those flavonoids that are slowly degraded because rapidly degrading flavonoids are less likely to be absorbed intact. Keywords: Flavonoids; microbial degradation; structure−activity